2018
DOI: 10.1001/jamacardio.2018.1717
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Combined Genetic and Lifestyle Risks With Incident Cardiovascular Disease and Diabetes in the UK Biobank Study

Abstract: In this large contemporary population, genetic composition and combined health behaviors and factors had a log-additive effect on the risk of developing cardiovascular disease. The relative effects of poor lifestyle were comparable between genetic risk groups. Behavioral lifestyle changes should be encouraged for all through comprehensive, multifactorial approaches, although high-risk individuals may be selected based on the genetic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
292
3
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 409 publications
(311 citation statements)
references
References 48 publications
12
292
3
4
Order By: Relevance
“…Cox regression analysis was performed to investigate the association between different sedentary behaviours and new-onset CAD events. CAD was defined based on ICD-9 and ICD-10 codes, together with operation codes and self-reported data on myocardial infarction, other ischaemic heart disease and history of coronary artery bypass grafting or percutaneous coronary intervention as performed previously 44 . Three Cox regression models were used to investigate the association of leisure sedentary television watching, leisure computer use and driving with CAD; potential confounders were selected per prior epidemiological analyses 8 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cox regression analysis was performed to investigate the association between different sedentary behaviours and new-onset CAD events. CAD was defined based on ICD-9 and ICD-10 codes, together with operation codes and self-reported data on myocardial infarction, other ischaemic heart disease and history of coronary artery bypass grafting or percutaneous coronary intervention as performed previously 44 . Three Cox regression models were used to investigate the association of leisure sedentary television watching, leisure computer use and driving with CAD; potential confounders were selected per prior epidemiological analyses 8 .…”
Section: Methodsmentioning
confidence: 99%
“…Smoking status was defined as ideal (never smoked or quit >12 months ago), intermediate (quit smoking ≤12 months ago) or poor (current smoker). Physical activity was based on questionnaires concerning do-ityourself and exercise activities using guidelines for ideal cardiovascular health and according to previous research 44 . In short, physical activity was defined as ideal if participants had ≥150 min/week moderate or ≥75 min/week vigorous or 150 min/ week mixed (moderate and vigorous) activity.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that age, male sex, hypertension, DM, valvular heart disease, heart failure, coronary artery disease, CKD, in ammatory disease, obstructive sleep apnoea syndrome and smoking are common risk factors for AF and ischaemic stroke [9,11,12]. Potential risk factors, such as obesity and metabolic syndrome, contribute to the development of AF and atrial cardiomyopathy through a variety of mechanisms [13]. The Framingham Heart Study [14] pointed out that the lifetime risk of AF was approximately 20% with an optimal risk pro le, lower than that with a high-risk pro le (38.4%).…”
Section: Discussionmentioning
confidence: 99%
“…1 In order to improve established risk scores, a detailed battery of questionnaires, genetics, biochemical analyses and imaging is currently applied in large cohorts involving 200,000 individuals (German National Cohort) 20 or in the UK Biobank Study involving >500,000 individuals. 21,22 This will certainly improve the definition of individual risk beyond the established cardiovascular risk factors and first results have been presented. [21][22][23] However, importantly, this knowledge will have to be integrated into lifestyle preventive strategies.…”
mentioning
confidence: 99%
“…21,22 This will certainly improve the definition of individual risk beyond the established cardiovascular risk factors and first results have been presented. [21][22][23] However, importantly, this knowledge will have to be integrated into lifestyle preventive strategies. Characterization of ''basic'' biomarkers with prognostic potential to predict high-risk patients will have to be added by the identification of ''modifiable biomarkers'', which characteristically change by intervention strategies and predict efficacy of intervention.…”
mentioning
confidence: 99%